Design of polymer coated magnetic nanoparticles for the selective isolation of bacteria from mixed populations - Petch, Joshua Edward (2020)
The ability to selectively sequester bacteria from a mixed population is a desirable aim across a range of fields. Already some technologies exist to attempt to meet these aims however, these are generally limited to the confinement of small populations in defined locations and may be unable to differentiate between morphologically similar but phenotypically distinct cells. Furthermore, the use of immunomagnetic nanomaterials is likely to be prohibitively expensive for many scaled-up applications.